Master in Spatial Planning Specialisation: Environmental Conditions in Spatial Planning (Warsaw University of Technology) - Mironowicz, Izabela; Lo Piccolo, Francesco; Galland, Daniel (AESOP, 2018)
After a thorough examination of its contents and methods, the MSc in Spatial Planning Specialisation: Environmental Conditions in Spatial Planning offered by the Warsaw University of Technology has been highly distinguished with the AESOP CERTIFICATE OF QUALITY We certify that: This programme fulfils the European quality standards of planning programmes according to the AESOP Charter, complemented by an effective internationalization of teaching and learning processes
Warsaw University of Technology 52.22133919725185, 21.008589952001767 https://ror.org/00y0xnp53